2022
DOI: 10.1128/jcm.00646-21
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore Sequencing for Mycobacterium tuberculosis: a Critical Review of the Literature, New Developments, and Future Opportunities

Abstract: The next-generation short-read sequencing technologies that generate comprehensive, whole-genome data with single-nucleotide resolution have already advanced tuberculosis diagnosis, treatment, surveillance and source investigation. Their high costs, tedious and lengthy processes, and large equipment remain major hurdles for research use in high tuberculosis burden countries and implementation into routine care. The portable next-generation sequencing devices developed by Oxford Nanopore Technologies (ONT) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Ser315Thr has been widely demonstrated to be a high-confidence and frequent polymorphism that confers an INH-resistance signature of MTB [ 16 ], which was consistently characterized in our study through results of ONT sequencing. It was reported that most INH-resistant isolates harboring the Ser315Thr variant had an MIC of > 5 µg/mL [ 17 ], whereas nucleotide polymorphisms within other INH-resistant isolates with high MIC values have been sparsely investigated.…”
Section: Discussionsupporting
confidence: 62%
“…Ser315Thr has been widely demonstrated to be a high-confidence and frequent polymorphism that confers an INH-resistance signature of MTB [ 16 ], which was consistently characterized in our study through results of ONT sequencing. It was reported that most INH-resistant isolates harboring the Ser315Thr variant had an MIC of > 5 µg/mL [ 17 ], whereas nucleotide polymorphisms within other INH-resistant isolates with high MIC values have been sparsely investigated.…”
Section: Discussionsupporting
confidence: 62%
“…Owing to its advantages of real-time analysis, updated flow cells, long sequencing reads, reduced error rates, and accessibility of analysis software, nanopore sequencing has revived interest in the clinical application of TB diagnostics ( Dippenaar et al ., 2022 ). A previous study has demonstrated that nanopore sequencing could be a suitable alternative to NGS for the diagnosis of MTB and may be extensively adopted by public health laboratories ( Smith et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nanopore sequencing technology, developed by Oxford Nanopore, is a third-generation sequencing technology that is a potential alternative to NGS ( Smith et al ., 2020 ). The nanopore sequencing device is portable, can generate long sequence reads, and has data throughput that is comparable to that of NGS ( Dippenaar et al ., 2022 ). Nanopore sequencing is increasingly being used in TB, with previous studies demonstrating its excellent accuracy in predicting MTB resistance ( Cabibbe et al ., 2020 ;Cervantes et al ., 2020 ); however, its use in early TB screening is limited, particularly using clinical specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies ( Smith et al., 2020 ) have also shown Nanopore’s competitiveness in the diagnosis of drug-resistant TB. A recent review ( Dippenaar et al., 2022 ) showed that Nanopore’s low cost of sequencing combined with its portability and good performance makes it an attractive option for sequencing in research and clinical care settings. However, data on its application in the field of TB are limited, and there is no research on its application in the diagnosis of TP.…”
Section: Discussionmentioning
confidence: 99%